Hospital volumes and later year of operation correlates with better outcomes in acute Type A aortic dissection. (25th July 2017) - Geirsson, Arnar; Ahlsson, Anders; Franco-Cereceda, Anders; Fuglsang, Simon; Gunn, Jarmo; Hansson, Emma C; Hjortdal, Vibeke; Jarvela, Kati; Jeppsson, Anders; Mennander, Ari; Nozohoor, Shahab; Olsson, Christian; et al.
Abstract: OBJECTIVES: Acute Type A aortic dissection remains a life-threatening disease, but there are indications that its surgical mortality is decreasing. The aim of this report was to study how surgical mortality has changed and what influences those changes. METHODS: Nordic Consortium for Acute Type A Aortic Dissection is a retrospective database comprising 1159 patients (mean age 61.6 ± 12.2 years, 68% male) treated for acute Type A aortic dissection at 8 centres in Denmark, Finland, Iceland and Sweden from 2005 to 2014. Data gathered included demographics, symptoms, type of procedure, complications and 30-day mortality. RESULTS: The annual number of operations increased significantly from 85 in 2005 to 150 in 2014 ( P < 0.001). Chest pain was present in 85% of patients, 24% were hypotensive on presentation and 28% had malperfusion syndrome. Open distal anastomosis technique under hypothermic circulatory arrest was used in 85% of cases and its use increased significantly throughout the study. The 30-day mortality decreased from 24% in 2005 to 13% in 2014 ( P = 0.003). Independent predictors for 30-day mortality were preoperative cardiac arrest, malperfusion syndrome, Penn Class C, Penn Class B and C and cardiopulmonary bypass time, whereas later calendar year and higher hospital operative volumes predicted improved survival. CONCLUSIONS: Surgical mortality for acute Type A aortic dissection remains high but has decreased significantly over the last decade. This correlated with later year of operation and increased the number of operations performed per year, indicating that cumulative surgical experience contributes significantly to improved surgical outcomes.